Analysis of Women's Representation in Indonesian Films - Putri, Siti Aminah (Enigma in Cultural, 2023)
Film is a mass media that has a strong influence in shaping public perception. Representation of women in films can reflect the values and social norms that apply in society. This research aims to analyze the representation of women in Indonesian films. The method used is Roland Barthes' semiotic analysis model. Research data was obtained from three Indonesian films, namely "Marlina Si Pembunuh dalam Empat Babak", "Siti", and "Perempuan Berkalung Turban". The research results show that the representation of women in Indonesian films can be divided into two categories, namely: 1. Women as sexual objects. This representation shows women as weak, passive, and only as sexual objects. This can be seen in the film " Marlina Si Pembunuh dalam Empat Babak ", where Marlina is depicted as a weak woman who is a victim of rape. 2. Women as agents of change. This representation shows women as strong, independent, and able to act as agents of change. This can be seen in the films "Siti" and "Perempuan Berkalung Turban", where Siti and Annisa are depicted as female figures who dare to fight injustice and fight for women's rights.